APLIKASI PENDATAAN PASIEN RUJUK BALIK PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) BENGKULU - Ayu Mayang Sari; Asnawati Asnawati; Liza Yulianti (UNIVED Press, 2015)
This study discusses the building an application to refer the patient data through participant Social Security Agency (BPJS) Bengkulu using VB.Net. With this application, it is expected that patient data will follow behind the reconciliation program can be properly controlled. Data collection methods used in this research is the method of observation, interviews, and literature. The software used is Visual Basic .Net Programming Language of 2008 and the results obtained which can provide quick and accurate output. With this application is able to assist officers in providing services through more accurate reconciliation and appropriate to the participants. And assist officers in data processing became more organized.Keywords: Application Data Collection, VB.Net, participants BPJS